Quantitative chemical imaging with stimulated Raman scattering microscopy. (August 2017) - Fu, Dan
Highlights: SRS microscopy is a powerful chemical imaging technique for visualizing molecules based on their intrinsic vibrational signatures. SRS microscopy can quantitatively imaging lipids and proteins at high sensitivity, enabling applications in lipid biology and histopathology. Hyperspectral SRS imaging allows differentiation and quantification of endogenous molecules. Raman tags based on deuterium and alkyne have enabled SRS detection of previously 'hidden' molecules and reactions. Abstract : Chemical imaging plays an increasingly important role in studying heterogeneous biological systems. It combines molecular spectroscopy with high-resolution spatial information to create quantitative images of molecular distributions. Here I summarize recent progress in technical developments and biological applications of a specific chemical imaging technique—stimulated Raman scattering (SRS) microscopy. SRS microscopy allows for a wide range of molecules – both endogenous and exogenous – to be imaged at high spatial and temporal resolution in living cells, tissues, and organisms. I will focus on developments in SRS imaging that enable detection of non-fluorescent molecules and drive new biological applications.